Aktywność G. Juliusza Cezara w Hiszpanii w latach 60-tych I wieku przed Chr. - Ładoń, Tomasz (Collectanea Philologica, 2024)
In the sixties Caesar visited the Further Spain twice, first as quaestor (69–68), then as governor (with the rank of proconsul) in 61. Both stays are extremely important from the point of view of Caesar’s career and the activities carried out in the province. The author of the article examines Caesar’s activities in Spain: both his military actions and his administrative and financial activities. He looks at Caesar’s political connections, both those that brought him to Spain and those he managed to establish in the province.